Second one
<span>7/21
Hope it helps
</span>
6a. 1 - 2sin(x)² - 2cos(x)² = 1 - 2(sin(x)² +cos(x)²) = 1 - 2·1 = -1
6c. tan(x) + sin(x)/cos(x) = tan(x) + tan(x) = 2tan(x)
6e. 3sin(x) + tan(x)cos(x) = 3sin(x) + (sin(x)/cos(x))cos(x) = 3sin(x) +sin(x) = 4sin(x)
6g. 1 - cos(x)²tan(x)² = 1 - cos(x)²·(sin(x)²)/cos(x)²) = 1 -sin(x)² = cos(x)²
The answers are: D and C and A and E
because:
B 3(x - 5) - 2(6x2 + 9x + 5)=<span><span><span>−<span>12<span>x^2</span></span></span>−<span>15x</span></span>−<span>25
</span></span>F (4x2 - 13x - 7) - (16x2 + 9x - 5)=<span><span>−<span>12<span>x2</span></span></span>−<span>22x</span></span>−<span>2
E </span>(-15x2 + 9x - 10) + (3x2 - 10x - 5)=<span><span>−<span>12<span>x^2</span></span></span>−x</span>−<span>15</span>
Answer: 80
Step-by-step explanation: